2022
DOI: 10.1021/acssuschemeng.2c03530
|View full text |Cite
|
Sign up to set email alerts
|

Toward Economical Seawater-Based Methane Hydrate Formation at Ambient Temperature: A Combined Experimental and Computational Study

Abstract: Clathrate hydrates are emerging as a novel storage medium for safe and compact methane storage. However, their industrial-scale applicability is hindered by sluggish formation kinetics and intense energy cooling requirements. The present study is the first report on binary methane-tetrahydrofuran (THF) formation using the combination 1 of seawater and an unstirred reactor at ambient temperature (298.2 K) that would improve the process economics. Acidic zeolites with different Si/Al ratios (USY-40 and USY-10) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(197 reference statements)
0
2
0
Order By: Relevance
“…50−52 Molecular dynamics (MD) simulations have been often employed to investigate the microscopic behavior of gas hydrates from the molecular scale. 53−57 Based on MD simulation, some studies had reported that lignin, 58 protein, 47 humic acid, 59 fatty acid, 60 amino acid, 61 and other organic matters 62,63 exhibit different effects on the formation and growth of gas hydrate. Furthermore, some MD simulation results found that clay mineral surfaces can repel organic matter or form organo-mineral complexes, significantly influencing the wettability of the clay surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50−52 Molecular dynamics (MD) simulations have been often employed to investigate the microscopic behavior of gas hydrates from the molecular scale. 53−57 Based on MD simulation, some studies had reported that lignin, 58 protein, 47 humic acid, 59 fatty acid, 60 amino acid, 61 and other organic matters 62,63 exhibit different effects on the formation and growth of gas hydrate. Furthermore, some MD simulation results found that clay mineral surfaces can repel organic matter or form organo-mineral complexes, significantly influencing the wettability of the clay surface.…”
Section: Introductionmentioning
confidence: 99%
“…Park and coworkers observed that CH 4 hydrate solids can stably intercalate within montmorillonite interlayers under conditions of lower pressure and higher temperature, suggesting that a portion of such clay mineral surface actively involved in promoting CH 4 hydrate formation . Recently, Ren et al reported that montmorillonite shortens the induction time of gas hydrate formation by providing additional nucleation sites but retards the growth kinetics of gas hydrate due to hindered mass transfer. , Several experimental studies have found that the phase equilibrium of CH 4 hydrate is inhibited in porous media composed of solid particles. Our previous study revealed that clay surfaces affect gas hydrate formation by changing the concentration of guest molecules and ions via the adsorption of water molecules, ions, and guest molecules. , On the other hand, the abundant organic matter in hydrate reservoirs will also affect the formation behavior of gas hydrates. , Liu and coworkers found that organic matter can kinetically promote gas hydrate formation by enhancing gas–water contact, and this effect was further enhanced by sulfur-containing acid-dissolvable organic matters. , Some studies revealed that organic matter molecules inhibit the formation of gas hydrates by association with water molecules. , It is worth noting that recent studies have observed that organic matter and clay minerals have a synergistic effect on the formation of gas hydrates, which significantly shortens the induction time for gas hydrate formation. Molecular dynamics (MD) simulations have been often employed to investigate the microscopic behavior of gas hydrates from the molecular scale. Based on MD simulation, some studies had reported that lignin, protein, humic acid, fatty acid, amino acid, and other organic matters , exhibit different effects on the formation and growth of gas hydrate. Furthermore, some MD simulation results found that clay mineral surfaces can repel organic matter or form organo-mineral complexes, significantly influencing the wettability of the clay surface. , The interaction between organic matter and clay surfaces complicates the formation processes of gas hydrates.…”
Section: Introductionmentioning
confidence: 99%